ทุนทางจิตวิทยาทางบวก และบุคลิกภาพเชิงรุก ส่งผลต่อผลการปฏิบัติงาน โดยมีความผูกพันในงานเป็นตัวแปรสื่อ: กรณีศึกษา พนักงานขายในกลุ่มธุรกิจสื่อสารและโทรคมนาคม: Positive Psychological Capital, Proactive Personality, and Performance With Work Engagement as Mediator: a Case Study of Sale Persons in Telecommunication Company - วิชชาวุธ, ศุภชัย; แก้วกังวาล, ศรีเรือน (MBA-KKU Journal, 2019)
The purposes of this research were to study Psychological Capital, Proactive Personality, and Work Performance with Work Engagement as a mediator variable. The research tools consisted of questionnaire of Positive Psychological Capital, Proactive Personality, Work Engagement, and Work Performance. Statistical data analyzed by frequency, percentage, mean, standard deviation, Pearson’s correlation coefficient, Regression analysis, and the Sobel test. The result found that overall Positive Psychological Capital and its factors were positively and significantly correlated with Work Performance. (r = .368, r = .326, r = .330, r = .351, and r = .359 respectively). Proactive Personality was positively and significantly correlated with Work Performance. (r = .330). Overall Work Engagement and its factors were positively and significantly correlated with Work Performance. (r = .437, r = .431, r = .449, and r = .389 respectively). Work Engagement was a complete mediator variable of overall Positive Psychological Capital and its factors correlated with Work Performance. (Z = 4.223). And Work Engagement was a complete mediator variable of Proactive Personality, correlated with Work Performance. (Z = 4.746).